Printing in Plastic Build Your Own 3D Printer - Floyd Kelly, James. (Apress : Imprint: Apress, 2011)
Printing in Plastic: Build Your Own 3D Printer is your gateway into the exciting world of personal fabrication. The “printer” that you'll build from this book is a personal fabricator capable of creating small parts and other objects from drops of molten plastic. Design a part using a modeling tool such as Google SketchUp. Then, watch while the fabricator head sweeps back and forth and upwards, depositing plastic in all the right places. You can build anything from a replacement tab to hold a bookshelf in place, to a small art project, to a bashguard for your bicycle. If you can conceive it and design it, you can build it, and you'll have fun doing it! Printing in Plastic is aimed at creative people comfortable using power tools such as a table saw, circular saw, and drill press. Authors James Kelly and Patrick Hood-Daniel lead you through building a personal fabrication machine based upon a set of blueprints downloaded from their website. Example projects get you started in designing and fabricating your own parts. Bring your handyman skills, and apply patience during the build process. You too can be the proud owner of a personal fabricator—a three-dimensional printer. Leads you through building a personal fabrication machine capable of creating small parts and objects from plastic Provides example projects to get you started on the road to designing and fabricating your own parts Provides an excellent parent/child, or small group project.